Cis-1 Isomers of tethered bismethano[70]fullerene as electron acceptors in organic photovoltaics. Issue 33 (18th May 2018) - Umeyama, Tomokazu; Takahara, Shogo; Shibata, Sho; Igarashi, Kensho; Higashino, Tomohiro; Mishima, Kenji; Yamashita, Koichi; Imahori, Hiroshi
Abstract : cis -1 Isomers of [70]fullerene bis-adducts were utilized as electron-acceptors in organic photovoltaic devices for the first time. Abstract : Isomer-controlled [70]fullerene bis-adducts can achieve high performance as electron-acceptors in organic photovoltaics (OPVs) because of their stronger absorption intensities than [60]fullerene derivatives, higher LUMO energy levels than mono-adducts, and less structural and energetic disorder than random isomer mixtures. Especially, attractive are cis -1 isomers that have the closest proximity of addends owing to their plausible more regular close packed structure. In this study, propylene-tethered cis -1 bismethano[70]fullerene with two methyl, ethyl, phenyl, or thienyl groups were rationally designed and prepared for the first time to investigate the OPV performances with an amorphous conjugated polymer donor (PCDTBT). The cis -1 products were found to be a mixture of two regioisomers, α-1-α and α-1-β as major and minor components, respectively. Among them, the cis -1 product with two ethyl groups (Et2 - cis -1-[70]PBC) showed the highest OPV performance, encouraging us to isolate its α-1-α isomer (Et2 -α-1-α-[70]PBC) by high-performance liquid chromatography. OPV devices based on Et2 - cis -1-[70]PBC and Et2 -α-1-α-[70]PBC with PCDTBT showed open-circuit voltages of 0.844 V and 0.864 V, respectively, which were higher than that of a device with typical [70]fullerene mono-adduct, [70]PCBM (0.831 V) with a lower LUMO level. However, the short-circuit current densities and resultant power conversion efficiencies of the devices with Et2 - cis -1-[70]PBC (9.24 mA cm −2, 4.60%) and Et2 -α-1-α-[70]PBC (6.35 mA cm −2, 3.25%) were lower than those of the device with [70]PCBM (10.8 mA cm −2, 5.8%) due to their inferior charge collection efficiencies. The results obtained here reveal that cis -1 [70]fullerene bis-adducts do not guarantee better OPV performance and that further optimization of the substituent structures is necessary.